(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This paper provides a comprehensive overview of epidemiological trends in chronic diseases from a global perspective. Chronic diseases, including cardiovascular diseases, cancer, chronic respiratory diseases, and diabetes, are leading causes of mortality and morbidity worldwide. Using data from the World Health Organization and other sources, this paper examines the rising prevalence of chronic diseases, particularly in low- and middle-income countries undergoing rapid urbanization and lifestyle changes. Key risk factors such as tobacco use, unhealthy diets, physical inactivity, and environmental pollution are explored, along with social determinants of health that contribute to disparities in disease burden. The paper highlights the importance of multi-sectoral approaches to prevention and management, including policy interventions, healthcare system strengthening, and international collaboration. Despite progress, challenges such as limited access to healthcare services and inequities in health outcomes persist. The paper concludes by emphasizing the need for sustained efforts to address the global burden of chronic diseases and improve population health.